The intraday speed of adjustment of stock prices to earnings and dividend announcements - Patell, James M.; Wolfson, Mark A. (Journal of Financial Economics, 1984)
This paper examines the effects of Broad Tape news releases of earnings and dividend announcements on three aspects of intraday stock price behavior: mean returns, return variance, and serial correlation in consecutive price changes. The initial price reaction is evident in the first pair of price changes following the release (i.e., within a few minutes, at most). The returns earned by simple trading rules dissipate within five to ten minutes, although significant returns are detected in the overnight period and at the opening of trading on the next day. Disturbances in the variance and serial correlation persist for several hours and extend into the following trading day. As a class, dividend announcements induce much less activity than do earnings, although the response to dividend changes is comparable to the earnings announcement effect.